Constraints in Adoption of Extension Approaches by the Animal Husbandry Department as perceived by Veterinary Officers in Four Indian States - P., Lakshmi Manohari; Phand, Shahaji; Kareem, M.A. (Journal of Agricultural Extension Management, 2020)
India is blessed with vast livestock resources in the form of varieties of livestock breeds. According to the Livestock Census (2012), India's total livestock population was 512 million and poultry population was 729 million. The country ranks 1st in buffalo, 2nd in cattle & goats, 3rd in sheep and 5th in poultry population in the world. Over the last two decades, the livestock sector has grown significantly. Presently the country stands 1st in milk production, 2nd in Chevon (Goat meat), 5th in meat and 9th in poultry meat production in the world. However, the productivity and production remained untapped in the livestock sector due to several reasons. The average milk yield of Indigenous cattle is only 03.41 kg/day/ animal, that of crossbred cattle is 07.33 kg/day/animal and of Buffalo 04.80 kg/ day/animal. One of the major reasons is ineffective extension services by the animal husbandry extension personnel as well as other stakeholders. As per NSSO-2005 survey, only 5.1 per cent of livestock farmers are getting any kind of information as compared to 40 per cent farmers getting information on crop production. The present study was undertaken by MANAGE to explore the reasons for ineffective extension services in animal husbandry sector and to suggest appropriate policy measures.